Optimalisasi produksi kerajinan Sulam Tekat melalui pengembangan kemampuan SDM di bidang disain Kelompok Usaha Bersama (KUB) Kuntum Bertuah di Kelurahan Harjosari Kecamatan Sukajadi, Pekanbaru - Elva Susianti; Yusmar Palapa Wijaya; Tobi Arfan (Unri Conference Series: Community Engagement, 2019)
Harjosari Subdistrict, Sukajadi Sub-District is near from the central government of Pekanbaru. In this district, an UKM was established which was named Tekat Tiga Dara since 2009 with the first members of 2 (two) people and growi up to 10 (ten) people. This UKM produces and sells handicrafts produced by its members, including acrylic crafts, embroidery and aids. To remind the family income of the surrounding UKM, Nurila as the manager, formed two Craft Joint Business Groups (KUNTUM BERTUAH) and food (MEKAR BERSEMI). The KUB craft consists of 14 (fourteen) housewives who live around Jl. Dahlia gg. Jati. The main production from KUB Kuntum Bertuah is Sulam Tekat. Dense embroidery is a typical Malay embroidery that is widely applied to wall hangings, aisle, and souvenir for regional and wedding activities. The main ingredient of this dense embroidery is gold prada paper which is fixed (attached) to the base cloth (velvet, songket etc.). The process starts from making embroidery motifs on paper prada, cutting out motifs, pasting and sewing the edges of the motif with gold thread. The most difficult and time-consuming process is to embroider and make paper patterns. Making patterns on paper is done by tracing pattern on paper prada, then cut according to the curve of the pattern. Both of these processes requires high patience and precision. If it is wrongly cut, then this expensive material will be damaged and cannot be used. This KUB very hopeful for a tool that can print patterns and at the same time cut them on prada paper. To overcome this problem, KUB members will be trained to use simple graphic design computer applications commonly used to print it on cutting sticker printer machines. Hopefully, with this method, the work of making souvenirs with any of the same motifs can be made shorter and faster. It is expected that this KUB production will also increase according to market demand.